Tests for the assessment/correlation of pragmatic and grammatical competence in Sino-Spanish speaking students of Spanish - Gibert Escofet, M. Isabel; Gutiérrez-Colón Plana, Mar (Porta Linguarum An International Journal of Foreign Language Teaching and Learning, 2023)
This article presents a model for the evaluation of the pragmatic and grammatical competence of Spanish in Chinese-speaking students. Specifically, two tests are presented, both created especially for these students, and a pilot study is carried out to check if there is a correlation between the level of grammar and pragmatics in students of Spanish as a foreign language. The study has been carried out on a sample of 109 Chinese-speaking students of ELE and the tools used have been two level tests: one that exclusively measures grammar and that has been adapted from an already existing test. And a second one, which measures the level of pragmatic understanding of the students, and has been fully developed by the authors with all the requirements of a standardized test. Therefore, the result of this study is twofold: on the one hand, the tests are presented, so that they can be used by teachers; and on the other hand, a study that corroborates the fact that a good level of grammar does not necessarily imply a good level of pragmatic command of the language.